The Religious Horizon of Olivia Manning's Fortunes of War Novels - Perkin, J. Russell (Christianity & literature, 2025)
The conflict between Guy Pringle’s Marxism and the liberal individualism of his wife Harriet is central to Olivia Manning’s Balkan Trilogy and Levant Trilogy. Manning explores the condition of literal and spiritual homelessness produced by the Second World War within a variety of cultural, political, and religious contexts. The trilogies are not religious in a doctrinal sense, but the search for spiritual meaning is an important aspect of their representation of wartime.